A study of a modified design of dumbbell-shaped flux switching tubular linear generator for regular wave energy conversion. (May 2023) - Khatri, Pooja; Liu, Zhenwei; Rudolph, James; Wang, Xu
Abstract: Wave energy converters (WEC) use indirect drive hydraulic or turbine-type power take-off (PTO) mechanisms which consist of many moving parts, creating mechanical complexity and increasing the installation and maintenance costs. Linear generator-based direct drive wave energy converters could be a solution to overcome this problem, but the efficiency of the single conventional linear generator is not high enough, and it cannot work satisfactorily in the low-frequency range. In this paper, a novel dumbbell-shaped flux-switching linear generator has been proposed and studied as a power take-off unit for ocean wave energy conversion. The linear generator has a dumbbell-shaped stator, and the design is ameliorated by placing the permanent magnet rings of longitudinally alternating magnetic pole directions in the slots of its stator outer surface and is separated by thin wall steel ring shoulders. The linear generator also has a dumbbell-shaped translator. The stator is hollow where the translator slides inside axially inducing current in the coil. A long permanent magnet is inserted inside the hollow steel dumbbell core of the translator and a copper coil is wound around the outer surface of the moving translator core. The addition of permanent magnets on the outer slots of the stator is found to increase the output power significantly. To facilitate the investigation, the modified generator design has been compared to the conventional linear permanent magnet generator for their performances using the finite element method, as both machines are different in their structures. The results show that the double dumbbell-shaped flux-switching linear generator gives higher power output, magnetic flux density, branch current, and induced voltage. The double dumbbell-shaped flux-switching linear generator is then placed in a cylindrical buoy and investigated in a wave energy converter in the ocean environment. The hydrodynamic response of the cylindrical buoy has been investigated through ANSYS AQWA. The dynamic differential equations of the wave energy converter have been developed and solved for regular waves using Matlab codes. The peak output voltage, power, and the relative displacement of the linear generator translator with respect to the stator fixed with the buoy have been calculated through the Fourier Transform in the frequency domain using a Matlab code and through numerical integrations in the time domain using a Matlab Simulink code. The results in the time and frequency domains are compared and verified with each other. The relative displacement between the translator and stator buoy has been used as motion input of the ANSYS Maxwell simulation model, and the output voltage results of the ANSYS Maxwell simulation model have been compared and verified with those of the Matlab simulation models. The linear generator design in the wave energy converter under the regular wave excitation is further optimized for the maximum ratio of the peak output power to peak cogging force using the central composite design-based response surface method (RSM). The ANOVA analysis is used to validate the response surface model where its R 2 coefficient of 99.93% has indicated an excellent fit. The methods and results differ from those presented in previous studies.